2020
DOI: 10.1016/j.arthro.2020.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Can’t See the Right Forest Plot for the Wrong Trees!

Abstract: We have with great interest studied the meta-analysis and forest plot in Dwyer et al. 1 which is supposed to illustrate the effect of operative versus nonoperative treatment of femoroacetabular impingement syndrome. The meta-analysis, based on three randomized controlled trials, 2-4 shows a between-group difference on the International Hip Outcome Tool-33 (iHOT-33; 0 points [worst] to 100 points [best]), favoring operative treatment (mean difference: 3.46 points; 95% confidence interval [CI] 0.07 to 6.86). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In that study published in BMJ, "Arthroscopic Hip Surgery Compared With Physiotherapy and Activity Modification for the Treatment of Symptomatic Femoroacetabular Impingement: Multicentre Randomised Controlled Trial" by Palmer et al, 5 it happens that Palmer et al improperly measured and reported the International Hip Outcome Tool-33 on a visual analog scale using centimeters rather than millimeters. 2 One thing leads to another. Our award-winning researchers, Dwyer et al 3 not only cited Palmer et al 5 but quantitatively synthesized the results of the BMJ article in their meta-analysis.…”
Section: About That Lettermentioning
confidence: 99%
“…In that study published in BMJ, "Arthroscopic Hip Surgery Compared With Physiotherapy and Activity Modification for the Treatment of Symptomatic Femoroacetabular Impingement: Multicentre Randomised Controlled Trial" by Palmer et al, 5 it happens that Palmer et al improperly measured and reported the International Hip Outcome Tool-33 on a visual analog scale using centimeters rather than millimeters. 2 One thing leads to another. Our award-winning researchers, Dwyer et al 3 not only cited Palmer et al 5 but quantitatively synthesized the results of the BMJ article in their meta-analysis.…”
Section: About That Lettermentioning
confidence: 99%